1998
DOI: 10.1300/j067v17n01_11
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Content on Oppression

Abstract: MSW students' perceptions o f oppression, especially as it is taught in the Methods of Direct Practice sequence, were evaluated through qualitative and quantitative analysis. Findings revealed that students had knowledge of specific oppressed groups, especially racial and ethnic minorities, but were unable to link this group-specific undcrstanding to the overall influence of oppression on thc lives of people. The classroom environment, especially the perception of the profcssor as vulnerable/oppressed, was imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This assertion is true because some indigenous African cultures and beliefs are unjust: inequity and oppression like the hegemony of the patriarchal system, the deification of the male position, gender inequality and the land tenure system, need to be reformed and some aspects totally abandoned. But the family structure, the communalistic lifestyle, the concept of I and me, should be sustained and reformed (Deleuze, 1990; Foucault, 1997; Miehls and Moffat, 2000; Smith, 1997) along with the importance of micro- and macro-conceptions of societies in social work practice (Bronstein and Gibson, 1998; Moffatt, 1996; Swift, 1995).…”
Section: The Debate Dilemma Of Indigenizationmentioning
confidence: 99%
“…This assertion is true because some indigenous African cultures and beliefs are unjust: inequity and oppression like the hegemony of the patriarchal system, the deification of the male position, gender inequality and the land tenure system, need to be reformed and some aspects totally abandoned. But the family structure, the communalistic lifestyle, the concept of I and me, should be sustained and reformed (Deleuze, 1990; Foucault, 1997; Miehls and Moffat, 2000; Smith, 1997) along with the importance of micro- and macro-conceptions of societies in social work practice (Bronstein and Gibson, 1998; Moffatt, 1996; Swift, 1995).…”
Section: The Debate Dilemma Of Indigenizationmentioning
confidence: 99%
“…Finally, the attitudes of these Appalachian students may not reflect the attitudes of all White Americans. In fact, two case studies suggest some variance in the multicultural perspectives between Morehead State, Florida State and University of Michigan students (Lopez et al, 1995;Bronstein and Gibson, 1998). Conversely, these generalizibility concerns may be overstatements since studies of other commuter colleges have discovered similar distributions (Pohan, 1996;Tettegah, 1997;Levine and Curton, 1998).…”
Section: Limitationsmentioning
confidence: 99%
“…Despite some quantitative studies that have tangentially addressed social worker attitudes toward social diversity (Jayartne et al, 1992;Van Soest 1996;Bronstein and Gibson, 1998), there still…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, research exploring the extent to which anti-oppressive practice is embedded in the education and training of social work students has been conducted (Bronstein and Gibson, 1998; Coleman et al , 1999; Chand et al , 2002; Collins and Wilkie, 2010). Pointedly, Bronstein and Gibson’s (1998) study found that while course contents on oppression were gaining traction in the preparation of student social workers to embrace a social justice-oriented practice, they conclude that students were more likely to engage in clinical practice as against engaging in social justice advocacy and practice for which the course was designed in the first place. Similar findings were reported in the study by Chand et al (2002).…”
Section: Literature Reviewmentioning
confidence: 99%